THE CIRCULATION OF FEELINGS ON POLITICISED INSTAGRAM - Lehto, Mari; Mannevuo, Mona (AoIR Selected Papers of Internet Research, 2023)
In recent years a growing number of Finnish social media influencers have started to discuss political questions and even actors known for light lifestyle content have become vocal about social justice issues. In this paper, we explore how popular Finnish influencers experience the new expectations set for them and how they handle the mixture of intimate and algorithmic logics of Instagram. Our analysis draws from online observations of a wide range of lifestyle influencers and eight semi-structured, in-depth interviews with influencers and influencer agency representatives. Theoretically, we use Lauren Berlant’s (2008) analysis of ‘intimate publics’ to examine Instagram as a platform for vague intimacy, where feelings and commercial exchange flourish and circulate in proximity to the political.Our investigation into influencers’ experiences of politicised Instagram through the concept of vague intimacy reveals the complex interplay of authenticity, politics, values, commercialised exchange, intimacy and feelings. Our study shows that influencers’ social media engagement comprises mixed feelings and ambiguity as they struggle to manage their visibility and meet followers’ expectations. Their politically oriented content on Instagram intertwines with their everyday lives but not without a cost: their inboxes overflow with DMs from followers seeking meaningful discussion. Although influencers seek to make politics look easy and engage in meaningful conversations with their followers, balancing between inclusive politics, commercial visibility and protecting one’s own boundaries is hard work.